Pelatihan Autonomous Learning untuk Meningkatkan Kemampuan Bahasa Inggris Mahasantri Pondok Pesantren Tahfidzul Qur’an (PPTQ) Munzalan Mubarokan, Tanjungsari, Tulungagung - Emmi Naja; Mohammad Mashudi; Susanto Susanto (Jurnal Surya Masyarakat, 2026)
This Community Service Program (PKM) involved training and mentoring in autonomous learning for mahasantri (Islamic boarding school students at the tertiary level) at the Tahfidzul Qur’an Islamic Boarding School (PPTQ) Munzalan Mubarokan, located in Tanjungsari, Tulungagung. The program was initiated in response to the students’ aspirations to apply for scholarships and pursue higher education at overseas universities, which require a specific level of English language proficiency. However, students’ English proficiency was considerably below the required standard. Accordingly, this PKM aimed to enhance students’ English skills through autonomous learning training to support their improvement in English proficiency. This PKM employed a Community-Based Research (CBR) approach, implemented through four stages: laying the foundation, planning, gathering information, and acting on findings. The results indicated that the autonomous learning training had positive impacts, leading to improvements in both the students’ English proficiency and their motivation to learn English. Nonetheless, two main challenges emerged during implementation: the limited duration of the training and the students’ difficulties in accessing appropriate learning materials and resources. To address these issues, the PKM team provided ongoing monitoring to ensure students could engage in autonomous learning independently. It is important to note, however, that this PKM did not focus specifically on TOEFL/IELTS preparation, which is a common requirement for international scholarship applications. Therefore, future PKM are encouraged to focus on TOEFL/IELTS training to better support students in meeting the English requirements for scholarship applications and university admissions abroad.